How to diagnose neuropathy in diabetes mellitus? - Koçer, Abdulkadir (The European Research Journal, 2018)
Diabetic neuropathy is a common problem and can present various clinical presentations such as cranial neuropathy, radiculopathy, plexopathy, mononeuropathy, polyneuropathy and autonomic neuropathy. Clinical evaluation and use of scoring systems for the evaluation of diabetic polyneuropathy is an important step to get correct diagnosis. New informations about the diagnosis of diabetic neuropathy continue to emerge, which will lead to correct diagnosis and treatment as well. Diabetic length-dependent sensorimotor polyneuropathy (DSPN) and carpal tunnel syndrome are the most common seen problems. While acute and painful situations with motor weakness are mostly transient, sensory fibres are predominantly involved in chronic ones. Nerve conduction studies are needed to confirm diagnosis of any type of diabetic neuropathy, but they are normal in cases with small fiber involvement. The early diagnosis is crucial because it is well-known that subclinical diabetic neuropathy may be reversed or significantly improved with diabetes control. Because neuropathy at the stage in which only small fibers are affected can be reversed, it is important to diagnose DSPN in these stages. Skin biopsy taken from the dermatomal area of sural nerve, laser-doppler-imager flare technique, corneal confocal microscopy are used to assess small fibre dysfunction. The aim of the present review was to evaluate evidence-based diagnosis for any type of neuropathy seen in the patients with diabetes mellitus.